Landing errors in the men`s floor exercise are caused by flight characteristics - Marinsek, M.; Cuk, I. (Biology of Sport, 2010)
Landing errors on men`s floor exercises are caused by the flight parameters. Depending of the flight phase is determined the magnitude of the landing mistake. On the sample of all gymnasts (n=97) who were competing in the qualifications of the senior Men`s European Championships 2004 in Ljubljana, we analyzed saltos which were performed by them. Variables according to the theoretical model for the evaluation of salto landings in the floor exercise were used. From the mentioned model we chose only those variables that relate to the flight phase. Axis of rotation, number of turns around longitudinal axis and initial landing height have a significant impact on the magnitude of the landing mistake.